Molecular Sentinel-on-Chip for SERS-Based Biosensing - Wang, Hsin-Neng (2013)
The development of DNA detection techniques on large-area plasmonics-active platforms is critical for many medical applications such as high-throughput screening, medical diagnosis and systems biology research. Here, we report for the first time a unique “molecular sentinel-on-chip” (MSC) technology for surface-enhanced Raman scattering (SERS)-based DNA detection. This unique approach allows label-free detection of DNA molecules on chips developed on a wafer scale using large area nanofabrication methodologies. To develop plasmonics-active biosensing platforms in a repeatable and reproducible manner, we employed a combination of deep UV lithography, atomic layer deposition, and metal deposition to fabricate triangular-shaped nanowire (TSNW) arrays having controlled sub-10 nm gaps nanostructures over an entire 6-inch wafer. The detection of a DNA sequence of the Ki-67 gene, a critical breast cancer biomarker, on the TSNW substrate illustrates the usefulness and potential of the MSC technology as a novel SERS-based DNA detection method.